(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The use of phytochemical feed additives such as Maca (Lepedium meyenii) has been widely used by livestock farmers to reduce cost of production, toxic and residual effect of industrially chemical synthetic antibiotics and growth promoters. Therefore, this research was conducted to evaluate the effect of Maca power supplement on growth performance and nutrient digestibility of Yankasa rams. A total of twenty (20) grower Yankasa rams was divided into four treatment groups of 0, 5, 10, 15g/ Kg powdered Maca with five (5) rams each per treatment in a completely randomized design (CRD). The growth performance result revealed that all parameters were significantly (P<0.05) differences with the exception (P>0.05) of initial weight were T4 had the best growth performance attributes followed by T3. Profound (P<0.05) changes was recorded in Yankasa rams nutrient digestibility fed supplemented levels of Maca. There were significant (P<0.05) differences in feacal nitrogen, urine nitrogen, and nitrogen retained as percent feed intake while nitrogen intake and nitrogen retained were not significantly (P>0.05) affected with supplementation level of Maca. It could be concluded that Maca powder supplement has a profound effect of growth performance were T4 had the outstanding growth performance, considerable increases were recorded with increases level of Maca supplement on nutrient digestibility and nitrogen balances. For improvement of growth performance and nutrient digestibility, farmers are therefore recommended to supplement up to 15g/kg Maca powder into the diet of Yankasa rams, further studies are therefore recommended to fully explore its mechanisms of actions and nutritional activities.